Audience Perception of Forwarded Covid-19 Messages on Facebook and WhatsApp as Triggers of Misinformation - Dorcas, Nejo Temiloluwa (Budapest International Research and Critics University, 2025)
Misinformation is a problem that is much more prevalent in the social media than the traditional media. The social media is a sphere where individuals are both producers and consumers of information and so because of this a lot of information sent out during the Covid pandemic were sometimes misleading as individuals who sent out these messages have little or no regard for journalistic ethics. The impact of the covid-19 pandemic cannot be overlooked due to the flood of information that was spread about on the social network which could be false or true. The aim of the study is to find out if audiences consider the Covid-19 information from WhatsApp and Facebook as being credible and identify the perception of the audience on forwarded messages on Covid-19. The study adopts the Source Credibility as theoretical framework. The survey research method was adopted using questionnaire as the research instrument. The sample size for this study was 400 respondents selected from the total number of the population in Ikorodu; Maya and Ijede as study areas and only a total of 383 were collated and analyzed. The study used the stratified sampling technique. The findings show that majority of the audience make use of social media a lot and that during the Covid-19 pandemic they majorly got information from their social networks most especially WhatsApp, Twitter and Facebook and findings revealed that audience considers all Covid-19 related messages on their Facebook and WhatsApp pages credible enough and are likely to forward them but in the intent to inform and not deceive. This study recommends that users of social media should properly verify information before forwarding them as this will ensure that the problem of misinformation is curbed in order to avoid individuals making agitated decisions regarding their health as regards the Covid-19 pandemic and other issues arising.